Factors related to anxiety before surgery in children in urological operating rooms - Erlis Kurniasari; Nur Agustini (PAGEPress Publications, 2021)
This study aimed to determine the factors associated with preoperative anxiety in school-age children and adolescents at one of top hospital in the capital city of Indonesia. This study used analytical cross-sectional study. The selection of respondents used proportional stratified random sampling with a total of 86 respondents consisting of 43 school age children and 43 adolescents. Data analysis employed was the Chi-Square and Independent TTest. The results showed that anxiety was being experienced by 54.7% of respondents. In this study, it was found that there was a significant relationship (p<α) among children anxiety before surgery and age, family presence, previous operating experience and patient waiting time. Meanwhile, there was no significant relationship between gender and anxiety level before surgery in children. The results of this study can be used as the basis and reference for the hospital in making policies regarding efforts to manage anxiety before surgery in children. Accordingly, nurses could make appropriate nursing care interventions in preoperative patients to overcome preoperative anxiety experienced by schoolage children and adolescents.